2020
DOI: 10.26434/chemrxiv.12278318.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Wet-Dry Cycling on the Phase Behavior and Compartmentalization Properties of Complex Coacervates

Abstract: <div>Wet-dry cycling on the early Earth is thought to have facilitated production of molecular building blocks of life, but thus far its impact on self-assembly and compartmentalization of resulting (macro)molecules has been limited. We investigated dehydration/rehydration of complex coacervates, which are membraneless compartments formed by phase separation of polyelectrolyte solutions, and suggested as protocell models. Depending on initial composition of a poly(diallyldimethylammonium)/poly(acrylic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…It has been shown that LC-coacervate droplets disassemble (or transition to a different mesophase) when the salt concentration of the environment changes. One prebiotically plausible mechanism that could result in control of salt concentration is the dehydration rehydration cycle, also known as the wet-dry cycle [24]. Wet-dry cycles can occur geochemically through precipitation/evaporation events (caused by seasonal or diurnal cycles) [80] or through deliquescence [81].…”
Section: Relevance Of Lc-coacervates In Wet-dry Cyclesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that LC-coacervate droplets disassemble (or transition to a different mesophase) when the salt concentration of the environment changes. One prebiotically plausible mechanism that could result in control of salt concentration is the dehydration rehydration cycle, also known as the wet-dry cycle [24]. Wet-dry cycles can occur geochemically through precipitation/evaporation events (caused by seasonal or diurnal cycles) [80] or through deliquescence [81].…”
Section: Relevance Of Lc-coacervates In Wet-dry Cyclesmentioning
confidence: 99%
“…Additionally, as wet-dry cycles are able to modulate analyte concentrations and salinities, they have been shown to potentially have played a role in the cyclical assembly and/or disassembly of primitive compartments, such as coacervates [24]. Upon subjecting a PLL/rDD mixed system, initially in a non-functional precipitate state, to dehydration, it was observed that eventual stepwise transitions into (potentially functional) LC-coacervate droplets, (potentially semi-functional) ISO droplets, and then to a non-functional uniform phase occurred (black arrows in Figure 3C).…”
Section: Relevance Of Lc-coacervates In Wet-dry Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the concentration dependence of supramolecular assemblies was assessed using dilution experiments, wherein the assembled protein structures were diluted with buffered solution, and equilibrium FRET ratios were measured ( Figure S14 ). If proteins dynamically exchange with nearby protein partners in solution (which has been reported for electrostatically-driven complex coacervate formation), 63,64 then the dominant assembled structure is expected to depend on solution composition and protein concentration. For assemblies between proteins with relatively small net charges (e.g., those involving Ceru+15 variants), our results show that the FRET ratio decreased with decreasing protein concentration, suggesting rapid dynamic subunit exchange in solution.…”
Section: Resultsmentioning
confidence: 96%
“…5,118 An excess of long-chain fatty alcohols form oil droplets, and the oil may disrupt membranes. In addition, phase-separated coacervates could have served as another type of prebiotic compartment, 119,120 and fatty acid membranes may have even assembled around such coacervate compartments. 121 ■ CONCLUSIONS Fatty acids can assemble into membranes and could have formed the boundaries for the first cells.…”
Section: ■ Alternative Amphiphilesmentioning
confidence: 99%